2017
DOI: 10.1097/mib.0000000000001121
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable Risk Factors for Hospital Readmission Among Patients with Inflammatory Bowel Disease in a Nationwide Database

Abstract: Background Prior studies suggest that disease activity alone does not reliably predict hospital readmission among patients with inflammatory bowel diseases (IBD). Using a national database, we aimed to further describe the burden of readmissions for IBD and identify modifiable risk factors. Methods We performed a retrospective cohort study using 2013 data from the Nationwide Readmission Database (NRD). Using International Classification of Diseases-9th Revision, Clinical Modification (ICD-9-CM) codes, we ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 34 publications
1
57
0
1
Order By: Relevance
“…By contrast, larger studies have nearly all reported strong associations between depression and a worse IBD course. In database studies, a pre‐existing diagnosis of clinical depression is associated with adverse outcomes in IBD . A recent high‐quality prospective cohort study of 4314 patients with IBD over 2 years found significant associations between depressive symptoms and increased risk of multiple adverse outcomes, including relapse, hospitalization, requirement for biologicals and surgery .…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, larger studies have nearly all reported strong associations between depression and a worse IBD course. In database studies, a pre‐existing diagnosis of clinical depression is associated with adverse outcomes in IBD . A recent high‐quality prospective cohort study of 4314 patients with IBD over 2 years found significant associations between depressive symptoms and increased risk of multiple adverse outcomes, including relapse, hospitalization, requirement for biologicals and surgery .…”
Section: Epidemiologymentioning
confidence: 99%
“…By contrast, larger studies have nearly all reported strong associations between depression and a worse IBD course. In database studies, a pre-existing diagnosis of clinical depression is associated with adverse outcomes in IBD [34][35][36]. A recent high-quality prospective cohort study C. D. Moulton et al…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The bidirectional links between mental and physical health in IBD have also been established: Baseline IBD activity is associated with a nearly sixfold increase in the risk of anxiety over a period of 2 years, while anxious patients in IBD remission at baseline have a greater need for steroids, escalation of therapy, or IBD flare over time than those without anxiety. Moreover, the course of IBD is negatively affected by mental illness, resulting in more frequent flare ups, a more aggressive presentation, hospital readmissions, and increased risk of surgery …”
Section: Introductionmentioning
confidence: 99%
“…The bidirectional links between mental and physical health in IBD have also been established 5 : Baseline IBD activity is associated with a nearly sixfold increase in the risk of anxiety over a period of 2 years, while anxious patients in IBD remission at baseline have a greater need for steroids, escalation of therapy, or IBD flare over time than those without anxiety. Moreover, the course of IBD is negatively affected by mental illness, resulting in more frequent flare ups, 6,7 a more aggressive presentation, 8 hospital readmissions, 9 and increased risk of surgery. 10 Despite the high prevalence of mental illness in IBD 2 and the fact that the International IBD Guidelines 11 and the Australian IBD Standards (Standard A: High Quality Clinical Care) 12 recommend regular screening for distress and collaboration with mental health-care specialists in IBD management, recent studies demonstrated that only a fraction of patients reporting anxiety and depression receive the psychological or psychiatric help they need.…”
Section: Introductionmentioning
confidence: 99%